Redistribution carbon atoms in the surface layers of 30CRMNSIA steel after hot deformation - . Uazyrkhanova, G. K.; Skakov, M. K.; Popova, N. A. (Recent Contributions to Physics, 2013)
By electron microscopic analysis investigated character of distribution carbon atoms on different levels of 30CrMnSi steel surface layers (on surface, and at distance of 0.5 mm and 2 mm from surface) after deformation. 30CrMnSiА steel used as material of the rolling mill. It is shown that after rolling deformation of 30CrMnSi steel on the roll surface layers carbide transformations and carbon redistributions are observed. The carbon atoms from -α and - γ solid solutions go to formation of carbide phase particles and defects of crystal structure. Determined, that at distance of 2 mm from the roll surface carbon atoms in two different states: on defects of crystal lattice and carbide particles, which are located inside on boundaries and joints of fragments. Half of carbon is located on lattice defects. It is shown that at distance of 0.5 mm from roller surface between positions redistributed of carbon in carbide particles are located at boundaries and fragments joints. Also, between positions of carbon in the carbide particles are positioned inside fragments. Carbon atoms leave the crystal defects. As it approaches roll surface redistribution intensity of carbides ever more amplified. Established, that on roll surface carbon is entirely located in particles of special carbides, which are arranged at fragments boundaries and junctions and on lattice defects carbon absent. Thus (in the near-surface region of roll) in layer formation 0-0.5 mm carbide particles occurs due to carbon situated at lattice defects
Keywords: deformation; carbon atoms redistribution; carbide phase; fragmented substructure